(untitled) (Journal of Foreign Language Studies, 2019)
The article investigates the translation of Russian complex sentences with attributive clause containing the conjunction “откуда” into Vietnamese. It analyses examples of these sentences taken from Russian literature and its translated works into Vietnamese. The author categorizes syntactical transformations of source sentences and lexical transformations of the conjunction “откуда”, then points out the most frequently used. Thence, the article offers two strategies of translating Russian complex sentences with attributive clause containing the conjunction “откуда”, which can be used by learners of translation/interpreting courses as well as professional translators and interpreters.